2015
DOI: 10.1038/ajg.2015.358
|View full text |Cite
|
Sign up to set email alerts
|

Cost Utility of Competing Strategies to Prevent Endoscopic Transmission of Carbapenem-Resistant Enterobacteriaceae

Abstract: OBJECTIVES Prior reports have linked patient transmission of carbapenem-resistant Enterobacteriaceae (CRE, or “superbug”) to endoscopes used during endoscopic retrograde cholangiopancreatography (ERCP). We performed a decision analysis to measure the cost-effectiveness of four competing strategies for CRE risk management. METHODS We used decision analysis to calculate the cost-effectiveness of four approaches to reduce the risk of CRE transmission among patients presenting to the hospital for symptomatic com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 28 publications
1
22
0
2
Order By: Relevance
“…A cost-utility study suggests that at currently reported rates of endoscope associated infections, neither of these methods is cost-effective. 32 …”
Section: Discussionmentioning
confidence: 99%
“…A cost-utility study suggests that at currently reported rates of endoscope associated infections, neither of these methods is cost-effective. 32 …”
Section: Discussionmentioning
confidence: 99%
“…The enhanced pre-cleaning steps add to the complexity of duodenoscope washing, and as such, may be at risk for errors of omission and commission. In addition, some of the current methods of duodenoscope-related infection control (duodenoscope culture and 48-hour sequester, and ethylene oxide gas sterilization) may result in unacceptably increased capital and labor costs 5. Similarly, liquid and gas-based sterilants have crucial technical and environmental considerations and limitations, including occupational health hazards from ethylene oxide gas, the potential for cosmetic or functional damage, and the ineffectiveness of the gas- and liquid-based chemical sterilants in penetrating biofilm and blood barriers (Centers for Disease Control and Prevention, Vital signs: Carbapenem-resistant enterobacteriacae [2013].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a medical device should be designed in a way that healthcare personnel can both fastidiously clean and successfully disinfect or sterilize the device, throughout the device's designated use life [ 211 ]. If a company does not properly validate their reprocessing method, then the FDA is likely to send them a warning letter.…”
Section: Medical Devicesmentioning
confidence: 99%